Making the Team : Case File 13 #2 - Savage, J. Scott 1963- (Jeffrey Scott) (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2013)
A mysterious private school has opened in town and Nick, Carter, and Angelo join forces with their rivals Angie, Tiffany, and Dana to uncover the mystery behind the school's inhumanly good football team.
Keywords: Monsters -- Fiction; Video recordings -- Production and direction -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Football -- Fiction; Scientists -- Fiction; Supernatural -- Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Horror & Ghost Stories; JUVENILE FICTION / Humorous Stories